Anatomical “C”-shaped double-bundle versus single-bundle anterior cruciate ligament reconstruction in pre-adolescent children with open growth plates - Siebold, Rainer; Takada, Tsuyoshi; Feil, Sven (Knee surgery, sports traumatology, arthroscopy, 2016)
To analyse the clinical, rotational and radiological (MRI) results of paediatric anatomical “C-shaped” double-bundle (DB) anterior cruciate ligament (ACL) reconstruction with anteromedial and posteromedial bundle compared to single-bundle (SB) ACL reconstruction.